2016
DOI: 10.3390/molecules21060769
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic Acid Attenuates Airway Inflammation and Hyperresponsiveness in a Murine Model of Asthma

Abstract: Rosmarinic acid (RA) has numerous pharmacologic effects, including anti-oxidant, anti-inflammatory, and analgesic effects. This study aimed to evaluate the preventive activity of RA in a murine model of asthma and to investigate its possible molecular mechanisms. Female BALB/c mice sensitized and challenged with ovalbumin (Ova) were pretreated with RA (5, 10 or 20 mg/kg) at 1 h before Ova challenge. The results demonstrated that RA markedly inhibited increases in inflammatory cells and Th2 cytokines in the bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 49 publications
(62 reference statements)
1
25
0
Order By: Relevance
“…Data of the present study showed that RA treatment exhibited anti-inflammatory effects as evidenced by a significant decrease in kidney level of proinflammatory marker TNF-α. Similar antiinflammatory effects of RA were obtained in different models of inflammatory diseases 11,62 . The anti-inflammatory properties of RA were proven to be attained through the inhibition of COX-2 and inhibition of production of inflammatory chemokines and cytokines 63 .…”
supporting
confidence: 77%
“…Data of the present study showed that RA treatment exhibited anti-inflammatory effects as evidenced by a significant decrease in kidney level of proinflammatory marker TNF-α. Similar antiinflammatory effects of RA were obtained in different models of inflammatory diseases 11,62 . The anti-inflammatory properties of RA were proven to be attained through the inhibition of COX-2 and inhibition of production of inflammatory chemokines and cytokines 63 .…”
supporting
confidence: 77%
“…RosA has been found to inhibit ovalbumin (Ova)-stimulated airway inflammation in a mouse model of asthma (Liang et al, 2016). The mitogen-activated protein kinases (MAPKs) regulate the synthesis and secretion of pro-inflammatory mediators during the inflammatory process, and their family contains three different stress-activated protein kinase pathways: p38, JNK, and ERK .…”
Section: Asthmamentioning
confidence: 99%
“…The mitogen-activated protein kinase (MAPK) family consisting of three different stress-activated protein kinase pathways namely p38, JNK and ERK, has been found to modulate the level of IL-5 and other cytokines during inflammation. Therefore, MAPK pathway can also be used as a potential molecular target for the treatment of chronic inflammatory diseases [ 14 ] (Fig. 1 ).…”
Section: Molecular Pathways Linked To Inflammationmentioning
confidence: 99%